Uji Stabilitas Kit Cair Tetrofosmin pada Berbagai Kondisi Penyimpanan - Yunilda, Yunilda; Widjaksana, Widyastuti; Saptiama, Indra (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
Tetrofosmin radiopharmaceutical compound that is being developed by PTRR BATAN for use as myocardial perfusion imaging agent and cancer diagnostic agent in nuclear medicine. The aim of this study is observe the stability of this liquid kits after stored in various condition to determine its expire date various condition. The stability test was done of 1 hour, 3 hours, 5 hours and 7 hours after labeling. The radiochemical was determined its radiochemical purity has to be ≥ 90 %. Analysis of radiochemical purity was carried out by separation method which using Sep-Pak C18 cartride. Storage condition of tetrofosmin kit was carried out at various temperatures as in the deep freezer (-800C), freezer (-180C), refrigerator (2-60C) and cool box (2-60C). The result showed that the liquid tetrofosmin kits stored in deep freezer, freezer, refrigerator were stable up to 23 months, 8 weeks and 4 days respectively. Simulation of stability test after stored in a cool box was done by observing the temperature of cool box, and the result showed that the temperature in the cool box was constant as in refrigerator for up to 24 hours. Tetrofosmin which has been labeled with technetium-99m can with stand up 7 hours. It is concluded that expiry date of liquid tetrofosmin kit related with storage temperature, the lower the temperature the longer the expiry date of the kits.